Effect of irrigation protocols on bone temperature control during guided implant surgery - Theo Gualdi Alves; Leonardo Hoffmann de Barcellos; Hélio Radke Bittencourt; Rogerio Belle de Oliveira; Eduardo Rolim Teixeira; Rosemary Sadami Arai Shinkai (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2023)
Objectives: This experimental laboratory study aimed to compare the effect of four external irrigation protocols on bone tissue heating during guided implant drilling. Methods: Forty perforations were made in ten bovine rib specimens using customized surgical templates. Four experimental groups (n=10/group) were tested: Control group = 10-ml syringe with 25°C saline solution, Group 1 = 10-ml syringe with 10°C saline solution, Group 2 = combined external irrigation using a handpiece and a 10-ml syringe with 25°C saline solution, and Group 3 = combined external irrigation using a handpiece and a 10-ml syringe with 10°C saline solution. The temperature was measured at cervical and apical points using K-type thermocouples, a digital thermometer, and a video recorder. Data were analyzed by ANOVA and Pearson's correlation coefficients (alpha=0.05). Results: The maximum temperature was 42°C (cervical) and 44°C (apical). No difference in temperature changes was found among groups, but the difference between bone specimens was statistically significant. Temperature and time were positively associated for most groups, mainly in the cervical region. Conclusions: All irrigation methods were equally effective in controlling the bone temperature in cervical and apical regions. However, longer drilling times caused a greater increase in temperature.